Advertising in a free society - Harris, Ralph; Seldon, Arthur (Hobart paper., 2014)
This new version of 'Advertising in a Free Society' is valuable reminder of the fundamental role advertising plays in society. Although the criticisms aimed towards it, which Ralph Harris and Arthur Seldon aimed to dispel over half a century ago, continue to gain support, policy makers and campaigners risk undermining our freedom if they continue this crusade against the advertising industry. We should celebrate the fact that advertising empowers the everyday shopper, rather than undermining both businesses and consumers through constraining the industry.